The di-iron RIC protein (YtfE) of Escherichia coli interacts with the DNA-binding protein from starved cells (Dps) to diminish RIC protein-mediated redox stress - Silva, Liliana S.O. (2020)
The RIC (repair of iron clusters) protein of Escherichia coli is a di-iron hemerythrin-like protein that has a proposed function in repairing stress-damaged iron-sulfur clusters. In this work, we performed a bacterial two-hybrid screening to search for RIC-protein interaction partners in E. coli. As a result, the DNA-binding protein from starved cells (Dps) was identified, and its potential interaction with RIC was tested by bacterial adenylate cyclase-based two-hybrid (BACTH) system, bimolecular fluorescence complementation, and pulldown assays. Using the activity of two Fe-S-containing enzymes as indicators of cellular Fe-S cluster damage, we observed that strains with single deletions of ric or dps have significantly lower aconitase and fumarase activities. In contrast, the ric dps double mutant strain displayed no loss of aconitase and fumarase activity with respect to that of the wild type. Additionally, while complementation of the ric dps double mutant with ric led to a severe loss of aconitase activity, this effect was no longer observed when a gene encoding a di-iron site variant of the RIC protein was employed. The dps mutant exhibited a large increase in reactive oxygen species (ROS) levels, but this increase was eliminated when ric was also inactivated. Absence of other iron storage proteins, or of peroxidase and catalases, had no impact on RIC-mediated redox stress induction. Hence, we show that RIC interacts with Dps in a manner that serves to protect E. coli from RIC protein-induced ROS.